Direct evidence of Fe(v) and Fe(iv) intermediates during reduction of Fe(vi) to Fe(iii): a nuclear forward scattering of synchrotron radiation approach1. Issue 34 (14th September 2015) - Machala, Libor; Procházka, Vít; Miglierini, Marcel; Sharma, Virender K.; Marušák, Zdeněk; Wille, Hans-Christian; Zbořil, Radek
<x xml:space="preserve">Abstract</x> Identification of unstable high-valent iron species in decomposition of ferrate(vi) advances the understanding of mechanisms by ferrates.